MANAJEMEN KEARIFAN LOKAL LUBUK LARANGAN DESA PANGKALAN INDARUNG KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Veraliza ' Veraliza; Zulfan Saam; Thamrin ' Thamrin (Program Pascasarjana Universitas Riau, 2014)
This research based on sustainability management of lubuk larangan by communityPangkalan Indarung Village. The purpose of this study was to analyze the managementprocess from planning, organizing, implementing and controlling of lubuk larangan bycommunity Pangkalan Indarung Village and determine the factors that affect thesustainability of the management lubuk larangan by community Pangkalan IndarungVillage District Kuantan Singingi. This research method is qualitative method with adescriptive explorative approach. The method used in this research is descriptiveexploratory qualitative approach that describes the process of sustainable localwisdom management of lubuk larangan. It also examines the factors that affect thesustainability of local wisdom management lubuk larangan by community PangkalanIndarung Village District Kuantan Singingi. The results of research showed that thecommunity Pangkalan Indarung Village been successfully managing lubuk larangansustainable management process that includes planning related to setting goals,strategies and development of management activities; related institutional aspects oftraditional institutional and organizational aspects of customs, duties and functions ofthe organization and coordination of organizational structure; implementation of therelated fish harvest event of lubuk larangan; and supervisory violations related to theprevention of customs agreements and illegal fishing. Sustainability management oflubuk larangan by community Pangkalan Indarung Village influenced by severalfactors, among other ecological factors related to ecological conditions lubuk laranganconformity with local fish habitat; socio economic factors associated lubuk latangan asa source for the construction of public facilities; Socio cultural factors related lubukarangan recognition as a right ulayat desa and adaptation of social capital inmanagement system of lubuk larangan; and factors related to the role of government tothe granting of legal and technical guidance on the conservation of river resources.